2022
DOI: 10.1007/s10120-022-01280-2
|View full text |Cite
|
Sign up to set email alerts
|

Response to neoadjuvant chemotherapy and survival in molecular subtypes of resectable gastric cancer: a post hoc analysis of the D1/D2 and CRITICS trials

Abstract: Background Epstein–Barr virus positivity (EBV+) and microsatellite instability (MSI-high) are positive prognostic factors for survival in resectable gastric cancer (GC). However, benefit of perioperative treatment in patients with MSI-high tumors remains topic of discussion. Here, we present the clinicopathological outcomes of patients with EBV+, MSI-high, and EBV−/MSS GCs who received either surgery only or perioperative treatment. Methods EBV and MSI sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Although MSI was found to be a positive prognostic factor in the post hoc analysis of the MAGIC and the CLASSIC trials, the use of perioperative or adjuvant chemotherapy was not effective or even potentially detrimental. The same results were confirmed in the post hoc analysis of the CRITICS study and the ITACA-S trial [93,94]. Similarly, in 2019 a meta-analysis further demonstrated that MSS patients could benefit from adjuvant chemotherapy [95].…”
Section: Molecular Characteristicsmentioning
confidence: 67%
“…Although MSI was found to be a positive prognostic factor in the post hoc analysis of the MAGIC and the CLASSIC trials, the use of perioperative or adjuvant chemotherapy was not effective or even potentially detrimental. The same results were confirmed in the post hoc analysis of the CRITICS study and the ITACA-S trial [93,94]. Similarly, in 2019 a meta-analysis further demonstrated that MSS patients could benefit from adjuvant chemotherapy [95].…”
Section: Molecular Characteristicsmentioning
confidence: 67%
“…Tumour samples from Cologne scored as MMR proficient (MMRP) were grouped together with MSS. MSI status of the tumour samples from the D1/D2 and CRITICS trials was published before [21]. A detailed description of the MSI analysis and MMR immunohistochemistry method for each of the three cohorts can be found in online supplementary materials.…”
Section: Msi and Mmr Assessmentmentioning
confidence: 99%
“…MSI expression has been reported as a predictor of chemotherapy efficacy and response to immune checkpoint inhibitors [ 48 ]. However, the benefit of perioperative chemotherapy in MSI-high (MSH-H) gastric cancer remains controversial, due to the limited number of these patients in various clinical studies [ 49 ].…”
Section: Microsatellite Instability (Msi) and Epstein-barr Virus (Ebv)mentioning
confidence: 99%
“…However, data on response rates to NAC in EBV+ resectable gastric cancer are limited [ 57 ]. In the CRITICS trial, among the molecular subgroups of gastric cancer, EBV+ tumors had the highest histopathologic response rate and better outcomes than EBV-/MSS tumors [ 49 ].…”
Section: Microsatellite Instability (Msi) and Epstein-barr Virus (Ebv)mentioning
confidence: 99%